The role of activated partial thrombin time in mediating the impact of poorly glycemic control on diabetic peripheral neuropathy in patients with type 2 diabetes mellitus - Zhang, Hui; Chen, Minghui; Sun, Lijie; Zhu, Wenwen; Niu, Tong; Fareeduddin Mohammmed Farooqui, Huzaifa; Wang, Hongxiao; Song, Bing; Wang, Jumei; Zhang, Haoqiang (Frontiers in Endocrinology, 2025)
AimThis study aims to investigate the role of activated partial thrombin time (APTT) as a potential mediator in the relationship between suboptimal glycemic control and diabetic peripheral neuropathy (DPN) in individuals with type 2 diabetes mellitus (T2DM).MethodsA total of 183 T2DM patients were enrolled in this study. Comprehensive clinical data, including coagulation parameters and nerve conduction velocity, were collected and compared between patients with and without DPN. Subsequent correlation and regression analyses were conducted to explore the associations among APTT, HbA1c levels, and nerve conduction velocities. Moreover, mediation analyses were performed to evaluate the total, direct, and indirect effects of HbA1c on specific nerve conduction velocities, with APTT serving as a mediator.ResultsIn comparison to 101 patients without DPN, 82 patients with DPN exhibited significantly elevated levels of HbA1c and decreased levels of APTT. Notably, levels of APTT and HbA1c were correlated with conduction velocities of Tibial nerve motor fibers, as well as sensory fibers of the Ulnar nerve, Median nerve, and Sural nerve. Furthermore, both elevated HbA1c and decreased APTT were identified as risk factors for DPN in T2DM individuals. Mediation analysis showed that APTT mediated the indirect effect of HbA1c on the conduction velocities of sensory fibers in both the ulnar nerve and sural nerve (95% CI: -0.3448, -0.0135; -0.3523, -0.0180). APTT mediated the relationship between HbA1c and the conduction velocities of sensory fibers in the ulnar nerve or sural nerve by 34.66% or 22.03%, respectively.ConclusionsIn patients with T2DM, uncontrolled HbA1c and shorter APTT emerges as risk factors for DPN. Additionally, the effect of increased HbA1c upon DPN, especially for influenced conduction velocities of sensory fibers in both the ulnar nerve and sural nerve may partly medicated by decreased APTT.